Analyse de l2019;Adoption du Mobile Banking dans une Economie en DE9;veloppement: Une Application au Cameroun (Global Journal of Management and Business Research, 2020)
The paper analyses the factors that explain the adoption of mobile banking services in a developing country The paradox of high penetration of mobile telephony and low consumption of mobile banking services raises questions For this reason after a literature review we used a logit regression on a sample of 156 respondents The main findings of the study indicate that the need for help with the use and the frequency of deposits and withdrawals negatively affect adoption Moreover the frequency of checking the account balance the number of banks with which the customer is related and the evaluation of the quality of the application are positively affecting the adoption of mobile banking
Keywords: mobile banking; financial innovation; adoption; developing country